Planning Of Septic Tank And Involvement For Household Waste Treatment For The Community In Nagarasari Kelurahan, Cipedes District, Tasikmalaya City - Oka Agus Kurniawan Shavab; Indra Mahdi; Empung Empung; Hendra Hendra; Albi Muhammad Fauzi; Taufik Ibrahim; Suci Panatagama Setiawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This service aims to increase public understanding of septic tank and infiltration planning for proper household waste treatment and in accordance with community needs. The problems found in the field are the capacity of the septic tank, the length, width and depth of the tank are not in accordance with the requirements, the slope of the bottom of the tank is not enough and with only one mud chamber, when sucking the mud it will smell because what is sucked in is mud that has not decomposed completely, and the lack of information about environmental diseases caused by poor handling of household waste. The implementation method in this service is carried out in a 5 W 1H way, namely solving problems from the questions: what, who, where, when, why, how. The planned activities that will be carried out are in collaboration with local health centers to carry out socialization and together with the community to build a septic tank design that is in accordance with the Indonesian National Standard (SNI). The solution to the problems found in the field is the provision of a stimulus in the form of repairing septic tanks and infiltration in partner areas, collaborating with the Cigeureung Health Center in the field of public health to disseminate public health regarding environmental health in household waste disposal, and collaborating with partners in the community service area. make a model of a septic tank in accordance with SNI.